SENSORY AND CHEMICAL CHARACTERIZATION OF COOKIES SUBSTITUTED WITH BLACK GLUTINOUS RICE FLOUR - Dina Ulmia; Safrida; Marniati; Sri Wahyuni Muhsin (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Cookies are a popular type of dry cake in Indonesia and are liked by various groups. Generally, cookies are made using wheat flour as the main ingredient, but black glutinous rice flour, which is rich in fibre and has health benefits, is chosen as an alternative substitute for wheat flour. This study aims to explore the effect of substituting black glutinous rice flour in cookies on organoleptic acceptance and nutritional content of the product. Objective: This study aims to identify the effect of substituting black glutinous rice flour on the organoleptic acceptance of cookies and to identify the effect of substituting black glutinous rice flour on the nutritional content of cookies.Method: This study uses an experimental method with a Completely Randomised Design (CRD). Organoleptic tests were conducted to assess parameters of colour, aroma, taste, crunchiness, and texture by using the Kruskal-Wallis test. Analysis of nutritional content using the anova test was carried out to measure the levels of water, ash, fat, protein, and carbohydrates in cookie products that use black glutinous rice flour as a substitute. Results: The results showed that there was a significant effect of adding black glutinous rice flour on the parameters of colour, aroma, taste, and crunchiness (P<0.05). However, there was no significant effect on the texture parameter (P>0.05). The nutritional content analysis showed that the water content of cookies varied, with the lowest value in P2 (4.98%), which almost reached the SNI standard limit (maximum 5%). Ash content increased with the increase in substitution of black glutinous rice flour, reaching the highest value in P4 (2.36%), which exceeded the SNI standard limit (maximum 1.8%). Fat content also increased, although it remained within the limits allowed by SNI (maximum 35%). Protein content slightly decreased in P2 (8.09%) compared to P1 (8.18%), showing no significant increase. Meanwhile, carbohydrate content decreased with the increase in substitution of black glutinous rice flour, with a significant difference between P1 (60.66%) and P2 (59.63%). Conclusion: Substitution of black glutinous rice flour in cookie production can improve organoleptic acceptance and nutritional content of the product, especially in terms of colour, taste, aroma, and crunchiness. The addition of black glutinous rice flour also affects the levels of water, ash, fat, protein, and carbohydrates, with the potential to increase the nutritional value and health benefits of the product.